The Estimation of the Expansion of Klaipėda Seaport from the Economic Point of View - Vasiliauskas, Aleksandras; Misiūnas, Algimantas (Ekonomika, 2000)
The estimation of the expansion of Klaipėda seaport in this paper is carried out only from the macroeconomic point of view: there arc estimated the influence of the expansion of Klaipėda seaport on the social and economic development of Lithuania and the common economic situation in Lithuania and abroad that determines possibilities of the realization of the expansion of Klaipėda seaport. The following main questions arc examined: • the influence of the existing Klaipėda seaport on the economy of Lithuania; • the influence of the expansion of Klaipėda seaport on the economy of Lithuania; • long-termed forecast of the Lithuanian export and import cargo flow through Klaipėda seaport; • long-termed forecast of the transit cargo flow through Klaipėda seaport; • financial possibilities of Lithuania for the realization of the expansion of Klaipėda seaport. The common conclusion is formulated that the expansion of Klaipėda seaport is purposive and necessary from the economic point of view and will make significant influence on the social and economic development of Lithuania. There are all prerequisites till 2030 year to ensure 60 million ton common flow of export, import, and transit cargo through Klaipėda seaport and financial possibilities to realise the expansion of Klaipėda seaport.